Транформація поняття та типології інформації в новому інформаційному законодавстві. - Кормич, Б.А.; Кормич, Б.А; Kormich, B (My University, 2012)
The present article provides the analyses of the modern Ukrainian legisla- tion to determine the essence of the term «information». The classiﬁ cation and principles of typology of information are also characterized. Besides, the major trends of the legal regulation of informational relations are formulated.
Кормич Б.А. Транформація поняття та типології інформації в новому інформаційному законодавстві. / Б.А.Кормич //Актуальні проблеми політики : зб. наук. пр. / гол. ред. С. В. Ківалов ; відп. за вип. Л. І. Кормич. – Одеса : Національний університет "Одеська юридична академія" : Південноукраїнський центр гендерних проблем, 2012. – Вип. 44. – C. 296 - 305.
Keywords: Інформаційне законодавство; Інформаційне право; Класифікація інформації; Правове поняття "інформація"; Правовое понятие "информация"; Классификация информации; Информационное право; Информационное законодательство; Information Legislation; Information Law; information classification; The legal concept of "information"